S‐Scheme Heterojunction TiO2/CdS Nanocomposite Nanofiber as H2‐Production Photocatalyst. Issue 24 (17th October 2019) - Ge, Haonan; Xu, Feiyan; Cheng, Bei; Yu, Jiaguo; Ho, Wingkei
Abstract: One‐dimensional (1D) nanostructured photocatalyst is a promising candidate for hydrogen (H2 ) generation, which can be used to deal with the energy crisis. Herein, novel 1D TiO2 /CdS well‐hybridized nanofibers (NFs) were synthesized via in situ electrospinning method. These 1D hybrid NFs showed a high H2 ‐production rate of 2.32 mmol h −1  g −1 with an apparent quantum efficiency of 10.14 %, which was 35‐fold higher than that of pristine TiO2 NFs. X‐ray photoelectron spectroscopy (XPS) analysis and density functional theory calculation implied that the electrons transferred from CdS to TiO2 upon hybridization and created an internal electric field (IEF) pointing from CdS to TiO2 . This IEF drove the photoexcited electrons in TiO2 to transfer toward CdS upon light irradiation as revealed by in situ irradiated XPS analysis, suggesting that a step‐scheme (S‐scheme) heterojunction was formed in the TiO2 /CdS nanohybrids and greatly promoted the separation of electron‐hole pairs to foster efficient H2 photogeneration. The significant enhancement of photocatalytic activity was also benefited from the easy transfer for electrons in the 1D well‐distributed nanostructure of nanohybrids. This work presents a method for in situ preparing well‐distributed 1D NFs with high photocatalytic activity for H2 production via the S‐scheme pathways. Abstract : Hard contact : The TiO2 /CdS S‐scheme heterojunction photocatalyst was prepared and showed highly photocatalytic H2 ‐production activity because efficient electron‐hole separation was achieved via S‐scheme mechanism.